Cultivation, cryopreservation and resuscitation of Theileria annulata transformed cells in serum-free media - Elati, Khawla; Zweygarth, Erich; Mhadhbi, Moez; Darghouth, Mohamed Aziz; Nijhof, Ard M. (Frontiers in Veterinary Science, 2022)
Introduction Tropical theileriosis is a protozoan disease caused by Theileria annulata that affects cattle in Northern Africa, the Middle East and Asia where vector ticks of the genus Hyalomma occur. Various measures are applied to control the disease, including vaccination with attenuated T. annulata schizonts. Cultivation of T. annulata schizonts is mainly conducted in media containing Fetal Bovine Serum (FBS), which has some disadvantages such as costs, batch- to-batch variation and ethical concerns. Methods In this study, we conducted three experiments to evaluate the ability of (1) T. annulata strains grown in RPMI with 10% FBS (RPMI-FBS) to adapt and grow in serum-free media (i.e., HL-1, RPMI without FBS supplementation, ISF-1, and M199), (2) a T. annulata strain grown in ISF-1 and subsequently frozen in this medium to grow in ISF-1 again after long-term storage in liquid nitrogen, and (3) a T. annulata strain freshly isolated from infected bovine lymphocytes to growin ISF-1, also after cryopreservation. Cell numbers, schizont index, the viability and generation doubling time were calculated in all experiments. Results and discussion In the first experiment, the Hessiene and Beja cell lines from Tunisia previously cultivated in RPMI-FBS and adapted to serum-free media continued to grow significantly better in RPMI-FBS compared to the serum-freemedia. In the second experiment, a Tunisian cell line (Hessiene) cryopreserved in ISF-1 with 5%[v/v] dimethylsulfoxide (DMSO) grewbetter after thawing in RPMI-FBS compared to ISF-1 with a highly significant difference in cell growth (p < 0.001), whereas the third experiment showed that the Ankara cell line had similar growth characteristics in both RPMI-FBS and ISF-1 before and after thawing, with a shorter generation doubling time in ISF-1 than in RPMI-FBS (p = 0.23). Our findings suggest that freshly isolated cells can be propagated, frozen and thawed in serum-free media such as ISF-1, but once cells are adapted to cultivation in the presence of FBS or resuscitated from frozen storage, propagation in serum-free media may not perform as well as cultivation in RPMI-FBS.